Organic solvent tolerant lipases - Baharum, Syarul Nataqain; Sulong, Mohamad Ropaning; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran (Nova Science Publishers, 2006)
The nature of the enzymes will be denatured in the presence of the organic solvents. Solvents not only affect enzyme stability but also change enzyme specificity. Most of the reports have been published concerning solvent stable enzymes. However, these enzymes are not naturally solvent stable enzymes that direct attempts from screening of organic solvent tolerant bacteria. In this chapter, we review the production and characterization of organic solvent tolerant lipases on the first attemps to screen organic solvent tolerant lipases from Bacillus sphaericus 205y, Bacillus sp. stain 42 and Pseudomonas sp. S5. All of these bacteria were proven to be organic solvent tolerant lipase producers. These lipases were stable in the organic solvents with log P value between 2.0 to 3.6. Organic solvent tolerant lipases from Pseudomonas sp. S5, B. sphaericus 205y, Bacillus sp. strain 42 were successfully purified to homogeneity. The optimum temperatures of these lipases were 45◦C, 55◦C and 70◦C, respectively. These purified lipases exhibited great stability and high activity in most of the organic solvents tested, therefore, these valuable criteria should not be neglected as important products in different fields could be developed from these lipases.